Designing for Scale and taking scale to account: lessons from a community score card project in Uganda - Ekirapa Kiracho, Elizabeth; Aanyu, Christine; Apolot, Rebecca Racheal; Namusoke Kiwanuka, Suzanne; Paina, Ligia (International journal for equity in health, 2021)
Planning for the implementation of community scorecards (CSC) is an important, though seldom documented process. Makerere University School of Public Health (MakSPH) and Future Health Systems Consortium set out to develop and test a sustainable and scalable CSC model. This paper documents the process of planning and adapting the design of the CSC, incorporating key domains of the scalable model such as embeddedness, legitimacy, feasibility and ownership, challenges encountered in this process and how they were mitigated. Methods: The CSC intervention comprised of five rounds of scoring in five sub counties and one town council of Kibuku district. Data was drawn from ten focus group discussions, seven key informant interviews with local and sub national leaders, and one reflection meeting with the project team from MakSPH. More data was abstracted from notes of six quarterly stakeholder meetings and six quarterly project meetings. Data was analyzed using a thematic approach, drawing constructs outlined in the project’s theory of change. Results: Embeddedness, legitimacy and ownership were promoted through aligning the model with existing processes and systems as well as the meaningful and strategic involvement of stakeholders and leaders at local and sub national level. The challenges encountered included limited technical capacity of stakeholders facilitating the CSC, poor functionality of existing community engagement platforms, and difficulty in promoting community participation without financial incentives. However, these challenges were mitigated through adjustments to the intervention design based on the feedback received. Conclusion: Governments seeking to scale up CSCs and to take scale to account should keenly adapt existing models to the local implementation context with strategic and meaningful involvement of key legitimate local and sub national leaders in decision making during the design and implementation process. However, they should watch out for elite capture and develop mitigating strategies. Social accountability practitioners should document their planning and adaptive design efforts to share good practices and lessons learned. Enhancing local capacity to implement CSCs should be ensured through use of existing local structures and provision of technical support by external or local partners familiar with the skill until the local partners are competent.
Keywords: Community Score Cards; Scale up; Accountability; Theory of change